Programme & abstracts unity in diversity : challenges in the new millenium : 6th International Conferences on Humanities and Social Sciences (ICHiSS 2014), 6th-7th June 2014, Royale Chulan Hotel, Kuala Lumpur
In 2014, The 6th International Conference on Humanities and Social Sciences 2014 (ICHiSS) will be held in Royale Chulan Hotel, Kuala Lumpur, Malaysia in conjunction with the Visit Malaysia Year 2014. National Defence University of Malaysia (NDUM) and Prince of Songkla University (PSU) puts strong emphasis on academic excellence with special focus in spurring the knowledge in the fields of social sciences and humanities such as politics, history, Islamic, culture and civilization studies. It provides a rare opportunity for our academicians to discuss humanity topics related to culture, politics, nation state, ethnic relation, business culture and issues related to management of ethnic community.